(untitled) (Pedagogical Horizons, 2025)
Due to the new research and teaching concept as well as the innovative learning-approach Urban Diversity Education (UDE) at the University and College for Teacher Education in Vienna, new collaborations between students and teacher educators are fostered. Participation in terms of designing and changing the environment, interdisciplinary collaborations with various institutions are long-term goals which highlight and celebrate diversity in society. This transformative approach is defined as service-learning (SL), also known by the Term Third Mission. In the university sector, it emphasizes student participation within the empowerment of learners and educators. Considering this, the authors of this article address the necessary resources, tools and networks by depicting examples of current research-projects leading to the practical implementation during student-courses at the Viennese University College of Teacher Education.